Additions to Bambusicolous Fungi of Savoryellaceae from Southwest China - Xian-Dong Yu; Sheng-Nan Zhang; Jian-Kui Liu (Journal of Fungi, 2023)
Asexual and sexual morphs of saprobic bambusicolous fungi were collected from freshwater and terrestrial habitats in Sichuan Province, China. Taxonomic identification of these fungi was carried out on the basis of morphological comparison, culture characteristics, and molecular phylogeny. Multi-gene phylogeny based on combined SSU, ITS, LSU, rpb2, and tef1α sequence data was performed to determine their phylogenetic placement, and the result showed that these fungi belong to Savoryellaceae. Morphologically, four asexual morphs are similar to Canalisporium and Dematiosporium, while a sexual morph well-fits to Savoryella. Three new species, Canalisporium sichuanense, Dematiosporium bambusicola, and Savoryella bambusicola are identified and described. Two new records, C. dehongense and D. aquaticum, were recovered from the bamboo hosts in terrestrial and freshwater habitats, respectively. In addition, the nomenclatural confusion of C. dehongense and C. thailandense is discussed.